Among the editorial policies of different countries and contexts, what effects do we produce and what effects do we wish for the research in Mathematics Education? - Miarka, Roger [UNESP]; Maltempi, Marcus Vinicius [UNESP]; Breda, Adriana; Farsani, Danyal; Bose, Arindam (FapUNIFESP (SciELO), 2023)
The purpose of this text is to unpack the diversity of editorial policies adopted for the circulation of research in Mathematics Education and the effects they produce on researchers and their research. For this, collaborators of the Bolema from Brazil, Spain, Norway and India were invited to describe the scenario of the editorial policies of their countries guided by questions such as: what are the editorial policies in your region? How do scientific journals sustain themselves? How are journals evaluated? What is expected of a researcher regarding their publication? Then, a discussion with the authors of the scenarios was carried out with the aim of revealing the effects of these policies, without the intention of producing converging opinions or exhaustiveness, driven by the question: Among the editorial policies of different countries and contexts, what effects do we produce and what effects do we wish for research in Mathematics Education?. The article is concluded with reflections on potential directions for editorial policies in research in Mathematics Education.
Entre as políticas editoriais de diferentes países e contextos, que efeitos produzimos e quais desejamos produzir para a pesquisa em Educação Matemática?
Keywords: Bolema; Scientific Journals; Scientific Metrics; Systems of Classification; Web Qualis